2009
DOI: 10.1590/s0037-86822009000400019
|View full text |Cite
|
Sign up to set email alerts
|

Sepse por Staphylococus aureus resistente à meticilina adquirida na comunidade no sul do Brasil

Abstract: O Staphylococcus aureus faz parte da microbiota natural, principalmente da pele, podendo tornar-se patogênico em condições como a quebra da barreira cutânea ou diminuição da imunidade. Os traumas que comprometem a integridade da barreira cutânea constituem-se na principal causa de mudança de comportamento deste microrganismo, para o agente etiológico mais comum de infecções cutâneas 1 2 6 .As infecções mais comuns envolvem a pele (celulite, impetigo) e feridas em sítios diversos. Algumas infecções por Staphylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 13 publications
0
15
0
6
Order By: Relevance
“…In 2009, for example, two cases of skin and soft tissue infection caused by CA-MRSA were reported in the city of Porto Alegre. 19,20 In the same year, Rozenbaum et al reported the case of 10-year-old non-immunocompromised girl, who had been admitted to a hospital in the city of Rio de Janeiro in 2007, presenting clinical manifestations of septic shock, and from whom MRSA was isolated. Seven days before admission, the patient had developed furunculosis involving the buttocks and cellulite in the left thigh; and she had no history of previous hospitalization or healthcare-associated procedures in the last year.…”
Section: Discussionmentioning
confidence: 99%
“…In 2009, for example, two cases of skin and soft tissue infection caused by CA-MRSA were reported in the city of Porto Alegre. 19,20 In the same year, Rozenbaum et al reported the case of 10-year-old non-immunocompromised girl, who had been admitted to a hospital in the city of Rio de Janeiro in 2007, presenting clinical manifestations of septic shock, and from whom MRSA was isolated. Seven days before admission, the patient had developed furunculosis involving the buttocks and cellulite in the left thigh; and she had no history of previous hospitalization or healthcare-associated procedures in the last year.…”
Section: Discussionmentioning
confidence: 99%
“…10 Fatores como internação em unidades de terapia intensiva (UTIs), hospitalização prolongada, procedimentos invasivos e exposição repetida a antibióticos propiciam o contato com o agente. 11,12,13 A presença de determinados microorganismos em fômites hospitalares pode indicar condições higiênicosanitárias insatisfatórias, representando, também, uma importante fonte de transmissão de enfermidades. 14 Frente a isso, o presente trabalho tem o propósito de analisar a presença de S. aureus nas maçanetas das portas dos quartos hospitalares, por ser um fômite que proporciona, de forma facilitada, a transmissão de tal agente infeccioso.…”
Section: Introductionunclassified
“…Several countries reported their presence as an emerging pathogen, including the United States, Australia, New Zealand, Samoa, several EU countries (Ribeiro et al, 2005) and South America (Brazil, Uruguay and Colombia) (Alvarez et al, 2006). In Brazil there are several case reports confirming the presence of this pathogen in the community involving cases of furunculosis (Razera et al, 2009), metastatic infections with major complications (Strong et al, 2008) and pneumonia (d 'Azevedo et al 2009;Gelatti et al, 2009). …”
Section: Case Reportsmentioning
confidence: 99%
“…The treatment was maintained with www.intechopen.com teicoplamin for 36 days, and from day 7 with meropenem for 14 days, showing progressive improvement and was discharged after 72 days from the hospital. No family member was colonized by CA-MRSA (d 'Azevedo et al, 2009). …”
Section: Case Reportsmentioning
confidence: 99%
See 1 more Smart Citation